Mosque-Based Eco-Social Welfare: the Case of ‘Brigade Bersih Masjid’ Program in Sragen - Paraswati, Ramita; Rosyid, Muhammad (Analisa: Journal of Social Science and Religion, 2025)
This study explores the role of Muslim scholars and community leaders in promoting environmental sustainability through mosque-based initiatives. Focusing on Al-Falah Mosque in Sragen, it examines the "Brigade Bersih Masjid" (BBM) program, which cleans one mosque per day to enhance cleanliness, improve mosque management, and foster public awareness of maintaining worship spaces as part of Islamic practice. Using a qualitative case study approach, this research incorporates field observations, interviews with the project manager, and analysis of program reports. Applying eco-social policy theory highlights the integration of environmental policies with religious principles. The findings suggest that religious eco-social policies can be implemented effectively by merging environmental awareness, policy frameworks, and religious teachings within mosque activities. Beyond the BBM initiative, Al-Falah Mosque has adopted sustainable practices such as solar panel installation, green landscaping, energy-efficient ventilation, and biogas production from sacrificial animal waste. Strengthening these efforts through philanthropic collaborations can further support operational sustainability and infrastructure development. This study contributes to the discourse on religious environmentalism by demonstrating the role of mosques in shaping ecological awareness. It underscores mosque-based activism as a key element of religious environmental education and its potential to cultivate eco-friendly worship practices within local communities.